Scanning agroforestry-based solutions for climate change mitigation and adaptation in Europe - Hernández-Morcillo, Mónica; Burgess, Paul J.; Mirck, Jaconette; Pantera, Anastasia; Plieninger, Tobias (Elsevier, 2017)
Agroforestry, the integration of trees and shrubs with livestock and/or crops, can make a substantial contribution to mitigating and enabling adaptation to climate change. However, its full potential will only be achieved if the challenges to agroforestry implementation are identified and the most efficient and sustainable solutions are made widely known. Therefore, the aim of this paper is to explore these challenges and to determine the most suitable set of solutions for each challenge that combines local effectiveness with European scale relevance. We performed a two-step “solution scanning” exercise. First, the main challenges to sustainable agroforestry in Europe were identified through 42 participatory workshops with 665 local stakeholders. The solutions to each challenge were scanned and classified into either direct solutions (28) to address climate change or indirect solutions (32) that improve the sustainability of agroforestry. In a second step, the direct solutions were prioritized through expert consultation in terms of their potential benefits for mitigation and adaptation. The most commonly reported barriers were a lack of knowledge and reliable financial support to which the most widely suggested indirect solutions were agroforestry training programmes and the development of safe economic routes. The direct solutions considered as holding the greatest mitigation and adaptation potential were the adoption of practices capable to increase soil organic carbon pools and the implementation of multifunctional hedgerows and windbreaks respectively. Our solution scanning approach can inform the implementation of the European climate strategy in general and to the Common Agricultural Policy in particular by pointing to concrete climate beneficial actions.
Keywords: Climate change strategy; Common agricultural policy; Europe; Nature-based solutions